PELATIHAN PEMBUATAN ALAT PERAGA MATEMATIKA BERBASIS LINGKUNGAN UNTUK MENINGKATKAN KOMPETENSI GURU SD DALAM PELAKSANAAN KURIKULUM 2013 DI KOTA BENGKULU - Effie Efrida Muchlis; Dewi Rahimah; Syafdi Maizora (DHARMA RAFLESIA, 2018)
Learners are directly related to what the teacher in learning activities and become direct experience of learners. Learning gives real meaning to the learner. By providing props based on mathematical learning environment will give meaning to the other disciplines. By learning math using environment-based learning tools teachers will associate with other subjects. The use of instructional media in teaching and learning is still lacking although the schools have had excellent facilities. This is caused by lack of knowledge and skills of elementary school teachers in the city of Bengkulu in using objects that are available around the environment to be a source of learning, especially math used as props. One of the utilization of objects that exist around the environment in mathematics is a manufacture of environment-based learning tools. The method used is a demonstration, assignments, discussions and question and answer. Through this service activities gained six props is a digital clock, the positive and negative card, card number, card mirroring, square blocks and funnel Commission. The implications of this activity is that it can terbentukya props based math environment more creative, to other subject matter. The conclusion of this study is to improve the ability of teachers to use and utilize existing objects around the environment to be used as props in learning. Keywords: Training, Maths Props, Primary School Teacher